EXTRALINGUISTIC ISSUES IN INTERCULTURAL COMMUNICATION: WORLDVIEWS, CUSTOMS, NONVERBAL LANGUAGE AND THE ROLE OF SOCIETY - Ibodullayev Romil; Shamurodova Naima Muxtarovna (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
This article examines the extra linguistic dimensions of intercultural communication with a particular focus on worldview, customs, non verbal language, and the role of society. While linguistic proficiency is vital in cross-cultural contexts, effective communication also requires a deep understanding of cultural practices that extend beyond language. Drawing on theoretical perspectives from anthropology, sociology, and communication studies, the paper analyzes how different worldviews shape perception, how rituals and traditions reinforce identity, how customs and social norms regulate behavior, and how nonverbal communication conveys meaning across cultural boundaries. The discussion also highlights the influence of societal institutions in shaping communicative norms. Practical implications are explored in relation to education, diplomacy, and business, emphasizing the importance of cultural competence in today’s globalized world. The study concludes that intercultural effectiveness depends not only on linguistic ability but also on sensitivity to the symbolic, behavioral, and social dimensions of culture.